The Influence Of Practical Learning Methods On Islamic Religious Education Motivation Of Class IV Students Of Primary School 01 Muara Kemumu - Reka Amelia Lestari; Dewi Purnama Sari (CV Media Inti Teknologi, 2024)
Examining the degree to which students utilize practical learning strategies, their motivation to learn both before and after, and their learning results both before and after, are the main objectives of this study. to ascertain how using practical learning techniques affects students' motivation and academic performance. SDN 1 Muara Kemumu was the location of this study. the approach taken in experimental study that is quantitative. Fifty-nine pupils in class IV served as the study's sample. The skills/psychomotor assessment tests, questionnaires, and observation sheets were the study instruments. The t-test is a data analysis tool. Research findings: First, the application of the practical learning method is at a very high level; student learning outcomes are at a high level prior to the application of the practical learning method and in a very high category following its application; student learning outcomes are at a high level prior to and following the application of the practical learning method. Second, there is a relationship between student learning outcomes and learning motivation that results from the implementation of practical learning approaches.